2016
DOI: 10.1021/acs.langmuir.6b03288
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly, Dynamics, and Polymorphism of hIAPP(20–29) Aggregates at Solid–Liquid Interfaces

Abstract: The misfolding and subsequent assembly of proteins and peptides into insoluble amyloid structures play important roles in the development of numerous diseases. The dynamics of self-assembly and the morphology of the resulting aggregates critically depend on various environmental factors and especially on the presence of interfaces. Here, we show in detail how the presence of surfaces with different physicochemical properties influences the assembly dynamics and especially the aggregate morphology of hIAPP(20-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 64 publications
4
34
0
Order By: Relevance
“…Furthermore, it was previously observed that purely electrostatic adsorption of native hIAPP(20–29) at a negatively charged mica surface results first in the adsorption of monomers in an upright conformation that is stabilized by intermolecular β-sheets and finally in enhanced fibrillization. 22 This is also observed in the AFM images shown in Figure S8, where few short protofibrils are visible for the native fragment (+|-).…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…Furthermore, it was previously observed that purely electrostatic adsorption of native hIAPP(20–29) at a negatively charged mica surface results first in the adsorption of monomers in an upright conformation that is stabilized by intermolecular β-sheets and finally in enhanced fibrillization. 22 This is also observed in the AFM images shown in Figure S8, where few short protofibrils are visible for the native fragment (+|-).…”
Section: Resultssupporting
confidence: 68%
“…At the same time, low monomer adsorption and high lateral mobility are generally considered a prerequisite for amyloid assembly at solid–liquid interfaces. 21,22,24,72,73 This is evident from Figure S8, which shows large prefibrillar aggregates and a few protofibrils for native hIAPP(20–29). PM-IRRAS (Figure 5) reveals significantly increased β-sheet contents for all fragments compared to the assembly in bulk solution (Figure 2b).…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…To further probe the fiber-formation dependent “detergent-type” membrane disruption by human-IAPP, solid-state NMR experiments were performed on aligned lipid bilayers [128,129]. These NMR studies demonstrated that the C-terminal domain of human-IAPP plays a vital role in fiber formation [108], and thus human-IAPP-20–29 peptide fragment (SNNFGAILSS) which forms fibers [130], was used to demonstrate the membrane disruption process. 31 P NMR experiments on anode aluminum oxide (AAO) nanotubes revealed the fragmentation of aligned lipid bilayers in the presence of human IAPP-20–29 (Fig.…”
Section: Protein Aggregation and Amyloid Formation In A Membrane Envimentioning
confidence: 99%